Herzberg's maintenance factor satisfaction/dissatisfaction of library student assistants in U.P. Diliman Libraries - Garcia, Justina D.; Yang, Jackson V. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study is focused on the library student assistants at UP Diliman libraries using Herzberg's maintenance factor of satisfaction/dissatisfaction. A total of 62 library student assistants employed during the second semester of academic year 2003-2004 various libraries of the university. A survey determined the following: 1) profile of the respondents with regards to sex/gender, degree major (BLIS/non BLIS), year level in college, with financial assistance, library/unit assigned and length of service; 2) satisfaction/dissatisfaction of library student assistants based on Herzberg's maintenance factors satisfaction/dissatisfaction; 3) male and female library student assistants satisfaction/dissatisfaction and the significant differences between male and female satisfaction/dissatisfaction for each maintenance factor; 4) BLIS and non BLIS satisfaction/dissatisfaction and the significant differences between BLIS and non BLIS satisfaction/dissatisfaction for each maintenance factor; 5) with financial assistance and without financial assistance satisfaction/dissatisfaction and the significant differences between the two respondents satisfaction/dissatisfaction for each maintenance factor. Descriptive method of research was used to determine the objectives of the study.
Results of the study reveals that: 1.) U.P. Diliman libraries are dominated by female library student assistants composed of (74.2). More than half (67.7) of library student assistants are non-BLIS major. Library student assistants in UP Diliman libraries are composed largely of fourth year students (38.7). Majority of the respondents (67.7) did not received financial assistance. Most of the respondents (79.0) are from different unit libraries. Half (50) of the respondents were employed for about six months and above in the library. 2.) Library student assistants in UP Diliman libraries are "dissatisfied" based on Herzberg's maintenance factor. There are significant differences between the maintenance factor dissatisfaction of library student assistants. 3.) Male and female are both "dissatisfied" based on Herzberg's maintenance factors. There are significant differences in the dissatisfaction between male and female library student assistants for each maintenance factor. 4.) BLIS and non-BLIS major are both dissatisfied using Herzberg's maintenance factors between BLIS and non BLIS library student assistants. 5.) Students with financial assistance and without financial assistance are both dissatisfied to Herzberg's maintenance factors. There are significant differences in the dissatisfaction for each maintenance factors between with financial assistance and without financial assistance.
This study confirmed that Herzberg's maintenance factors of satisfaction/dissatisfaction is affected by the library student assistants' personal characteristics : gender (Male/Female), degree major (BLIS/non BLIS), with financial assistance and without financial assistance.
Several recommendations were drawn from the library supervisors that the researcher has interviewed to improve the motivation of library student assistants.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Libraries -- Students; Student library assistants -- Philippines -- Quezon City